Complete Genome Sequences of Three Moraxella osloensis Strains Isolated from Human Skin - Lim, Jae Yun (Genome Announc, 2018)
Here, we present the complete whole-genome sequences of three Moraxella osloensis strains with octylphenol polyethoxylate-degrading abilities. These strains were isolated from human skin.